2013
DOI: 10.1136/annrheumdis-2012-eular.2210
|View full text |Cite
|
Sign up to set email alerts
|

THU0245 Rituximab has a beneficial effect on lung function and skin fibrosis in patients with systemic sclerosis. An open label study

Abstract: Background Evidence suggests that B cells may play a role in fibrosis. We have previously shown that rituximab (RTX) may favorably affect lung function and skin fibrosis in patients with systemic sclerosis (SSc). Objectives To further assess efficacy and safety of RTX in SSc Methods Twenty five patients with diffuse SSc from two University Hospitals were recruited. All patients had evidence of lung involvement as indicated by findings in chest HRCT and pulmonary function tests (PFT). Patients received 4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
2
9
0
1
Order By: Relevance
“…The previously reported 6-month followup data of our study suggested that RTX was well tolerated and could safely be administered in patients with early dcSSc 16 . The 2-year followup data confirm this finding, as does work from other groups 13,14,15,17 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The previously reported 6-month followup data of our study suggested that RTX was well tolerated and could safely be administered in patients with early dcSSc 16 . The 2-year followup data confirm this finding, as does work from other groups 13,14,15,17 .…”
Section: Discussionsupporting
confidence: 82%
“…The safety and potential benefits of RTX in SSc have been evaluated 13,14,15,16,17 . But to date a 2-treatment course (months 0/6) of RTX in early diffuse SSc has not been investigated.…”
mentioning
confidence: 99%
“…The same study group conducted a posthoc analysis of this study, revealing that CD19-positive cell count and high mRSS predict favourable response to rituximab [15]. The use of rituximab for SSc with interstitial lung disease (SSc-ILD) seems effective based on previous reports [20–25]. Still the efficacy should be confirmed through randomized controlled clinical trials with a larger sample size.…”
Section: B Cell-targeted Therapymentioning
confidence: 84%
“…Supportive evidence of the efficacy of rituximab in SSc-ILD also came from a small sample size trial 141 and observational studies. [142][143][144] Collectively, these results indicate that patients with SSc-ILD benefit from rituximab treatment in terms of FVC, quality of life, and skin fibrosis, offering an effective treatment option for this group of patients at the expense of a manageable risk of infection. 138,140…”
Section: Rituximabmentioning
confidence: 86%